Application of the Principle of Functional Differentiation Within the Criminal Justice System Framework in Indonesia Through Law Number 20 Of 2025 on The Criminal Procedure Code - Irwansyah Irwansyah; Handrawan; Idaman Idaman (Journal of Law, Social Science and Management, 2026)
Background: The implementation of Indonesia's Criminal Justice System (CJS) faces numerous challenges stemming from the formalistic-dogmatic application of the Criminal Procedure Code (KUHAP). This rigid legal framework has resulted in procedural inflexibility, unresponsiveness to evolving legal needs, and various systemic inefficiencies including protracted legal proceedings, inadequate inter-institutional coordination among law enforcement agencies (police, prosecutors, judiciary, and correctional institutions), abuse of power, and overlapping jurisdictional authorities. The principle of Functional Differentiation represents a legal normative framework that mandates law enforcement officials to execute their duties based on professional and proportionate standards within the CJS. Objective: This study examines the regulation and implementation of the Principle of Functional Differentiation in Indonesia's CJS through Law Number 20 of 2025 concerning the Criminal Procedure Code. Method: The research employs a normative legal research methodology, utilizing statutory and conceptual approaches to analyze primary legal sources and doctrinal literature. Results: Findings indicate that the principle serves as a preventive mechanism against abuse of power and jurisdictional overlap while facilitating due process of law through clear separation of authorities among law enforcement agencies. This Division of Power framework establishes checks and balances between institutions, enabling the realization of an Integrated Criminal Justice System (ICJS). Conclusion: The study concludes that the Principle of Functional Differentiation, when implemented responsively and progressively, serves as the ideal legal foundation (recht ideal) for achieving the tripartite normative objectives of legal certainty, justice, and utility in Indonesia's criminal justice system.